2020
DOI: 10.1111/nph.16502
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground determinants and ecological implications of shrub species' degree of isohydry in subtropical pine plantations

Abstract: The degree of plant iso/anisohydry is a popular framework for characterising species-specific drought responses. However, we know little about associations between below-ground and above-ground hydraulic traits as well as the broader ecological implications of this framework.For 24 understory shrub species in seasonally dry subtropical coniferous plantations, we investigated contributions of the degree of isohydry to species' resource economy strategies, abundance, and importance value, and quantified the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 84 publications
2
10
0
Order By: Relevance
“…Intuitively, species with deeper rooting systems have a greater chance to capitalize on relatively stable water resources such as deep soil water or groundwater, so there will be less risk of experiencing negative water potential during protracted drought stress. This suggests that the rooting depth trait can be informative in predicting species-specific mortality vulnerability, especially for co-occurring species or individuals showing contrasting drought response ( Johnson et al, 2018b ; Li et al, 2018b ; Jiang et al, 2020 ). Interestingly, in a study conducted by Wu et al (2018) , the authors noted that the legacy effects of drought, as represented by the offsets between observed growth and predicted growth, persisted longer in deep-rooted trees compared with shallow-rooted functional types such as grasses or shrubs, indicating that deeper roots may compromise drought resilience, therefore questioning the role of deeper roots in facilitating overall fitness.…”
Section: Parameterizing Drought-induced Hydraulic Failure: What Trait...mentioning
confidence: 99%
“…Intuitively, species with deeper rooting systems have a greater chance to capitalize on relatively stable water resources such as deep soil water or groundwater, so there will be less risk of experiencing negative water potential during protracted drought stress. This suggests that the rooting depth trait can be informative in predicting species-specific mortality vulnerability, especially for co-occurring species or individuals showing contrasting drought response ( Johnson et al, 2018b ; Li et al, 2018b ; Jiang et al, 2020 ). Interestingly, in a study conducted by Wu et al (2018) , the authors noted that the legacy effects of drought, as represented by the offsets between observed growth and predicted growth, persisted longer in deep-rooted trees compared with shallow-rooted functional types such as grasses or shrubs, indicating that deeper roots may compromise drought resilience, therefore questioning the role of deeper roots in facilitating overall fitness.…”
Section: Parameterizing Drought-induced Hydraulic Failure: What Trait...mentioning
confidence: 99%
“…This limitation is particularly striking considering that the highly dynamic below-ground environment plays a crucial role in mediating plant water stress responses (Brunner et al, 2015;Phillips et al, 2016). Indeed, plant water-use strategies can shift within a species due to variation in rooting depth, root hydraulics and soil biotic interactions (Jiang et al, 2020;Kannenberg & Phillips, 2017;Matheny, Mirfenderesgi, et al, 2017). Inferences regarding plant water sourcing and below-ground behaviour are often limited by current model representations that treat the rhizosphere as a one-dimensional profile, with no lateral interaction or competition (Warren et al, 2014).…”
Section: Looking Below-groundmentioning
confidence: 99%
“…L p is however measured without normalization by the root size (eg. Jiang et al 2020 ). Finally, Tsuda et al showed a good correspondence between L o (plus the total plant conductance, K plant , and leaf conductance, K leaf ) as measured with an HPFM and the same parameters, but measured by another technique, the evaporative method (Tsuda and Tyree 2000 ).…”
Section: Current Experimental Approachesmentioning
confidence: 99%